LGG-13. PAPILLARY GLIONEURONAL TUMOR (PGNT) EXHIBITS A CHARACTERISTIC METHYLATION PROFILE AND MANDATORY FUSIONS INVOLVING PRKCA. (23rd April 2019) - Hou, Yanghao; Pinheiro, Jorge; Sahm, Felix; Pfister, Stefan M; Jones, David T W; Bertero, Luca; von Deimling, Andreas
Abstract: Papillary glioneuronal tumor (PGNT) predominantly arises in children, adolescents and young adults. Its diagnosis poses a major diagnostic challenge. Recently, SLC44A1-PRKCA fusions have been described in PGNT. We subjected 28 brain tumors from different institutions histologically diagnosed as PGNT to molecular analysis and morphological analysis. Array-based methylation analysis revealed that 17/28 tumors exhibited methylation profiles typical for other tumor entities, mostly dysembryoplastic neuroepithelial tumor and hemispheric pilocytic astrocytoma. Conversely, 11/28 tumors exhibited a unique profile thus constituting a distinct methylation class PGNT. By screening the extended Heidelberg cohort containing over 25000 CNS tumors, we identified three additional tumors belonging to this methylation cluster, but originally histologically diagnosed otherwise. RNA sequencing for the detection of SLC44A1-PRKCA fusions could be performed on 19 of the tumors, 10 of them belonging to the methylation class PGNT. In two additional cases, SLC44A1-PRKCA fusions were confirmed by FISH. We detected fusions involving PRKCA in all of the cases of this methylation class with material available for analyses: the canonical SLC44A1-PRKCA fusion was observed in 11/12 tumors, while the remaining case exhibited a NOTCH1-PRKCA fusion. Neither of the fusions was found in the tumors belonging to other methylation classes. Our results point towards a high misclassification rate of the morphological diagnosis PGNT and clearly demonstrate the necessity of molecular analyses. PRKCA fusions are highly diagnostic for PGNT and detection by RNA sequencing allows identification of rare fusion partners. Methylation analysis recognizes a unique methylation class PGNT irrespective of the nature of the PRKCA Fusion.